(untitled) (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2023)
The purpose of this review was to identify and synthesize the most important literature on the relationship between homophobia and sport, education, discrimination and/or exclusion and mental and/or physical health. For this purpose, the PRISMA methodology was used to identify, select, evaluate and synthesize the documents found in the following databases for English: Science Direct, Taylor & Francis Online, Web of Science and PubMed, and in Spanish, Scielo and Dialnet. The Unesco Thesaurus for Spanish and MesH for English were used to search for documents. Thus, the final review was based on 73 documents that met the criteria of inclusion due to temporality, elimination due to duplication and close relation with the subject matter under study. From this, it is reaffirmed how homophobia and sport are closely related in most of the studies analyzed, and from this identification conceptual approaches are derived through the study categories related to education. This documentary review leaves open the invitation to carry out many more investigations related to this problem in a closer way to the LGBTIQ+ community, given that it is necessary to emphasize processes of sensitization of the entire sports macro-structure, on issues related to sexual orientation, thus seeking to sow inclusive attitudes from sport, sports education and the social relationship that is established in it.